A micrococcal nuclease homologue in RNAi effector complexes. - Caudy, A.A.; Ketting, R.F.; Hammond, S.M.; Denli, A.M.; Bathoorn, A.M.; Tops, B.B.; Silva, J.M.; Myers, M.M.; Hannon, G.J.; Plasterk, R.H. (Nature, 2003)
RNA interference (RNAi) regulates gene expression by the cleavage of messenger RNA, by mRNA degradation and by preventing protein synthesis. These effects are mediated by a ribonucleoprotein complex known as RISC (RNA-induced silencing complex). We have previously identified four Drosophila components (short interfering RNAs, Argonaute 2 (ref. 2), VIG and FXR) of a RISC enzyme that degrades specific mRNAs in response to a double-stranded-RNA trigger. Here we show that Tudor-SN (tudor staphylococcal nuclease)--a protein containing five staphylococcal/micrococcal nuclease domains and a tudor domain--is a component of the RISC enzyme in Caenorhabditis elegans, Drosophila and mammals. Although Tudor-SN contains non-canonical active-site sequences, we show that purified Tudor-SN exhibits nuclease activity similar to that of other staphylococcal nucleases. Notably, both purified Tudor-SN and RISC are inhibited by a specific competitive inhibitor of micrococcal nuclease. Tudor-SN is the first RISC subunit to be identified that contains a recognizable nuclease domain, and could therefore contribute to the RNA degradation observed in RNAi.